Self-Tuning Fuzzy PID Controller Design for Aircraft Pitch Control - Wahid, Nurbaiti; Hassan, Nurhaffizah (2012 Third International Conference on Intelligent Systems Modelling and Simulation, 2012)
In this paper self-tuning fuzzy PID controller is developed to improved the performance for a pitch control of aircraft system. The controller is designed based on the dynamic modeling of system begins with a derivation of suitable mathematical model to describe the longitudinal motion of an aircraft. Fuzzy logic is used to tune each parameter of Proportional-integral-derivative (PID) controller by selecting appropriate fuzzy rules through simulation in Mat lab and Simulink. Comparative assessment based on time response specifications between conventional PID controller with self-tuning fuzzy PID for an autopilot of longitudinal dynamic in pitch aircraft is investigated and analyzed. Simulation results show that, the performance of a pitch control system has improved significantly using self-tuning fuzzy PID compared to conventional PID controller.